(untitled) (Bangladesh Journal of Psychology, 2024)
While existing documentation on the history of Psychology in Bangladesh provides some insights, it often lacks a comprehensive and current perspective on the discipline’s progress, prospects, and challenges. This paper aims to address these gaps by offering a thorough and up-to-date overview of Psychology’s development in Bangladesh, from its early 20th-century origin to its present state. It examines the development of Psychology through the historical contexts of British India, Pakistan, and modern Bangladesh, which are shaped by various socio-political, cultural, educational, and psychosocial factors. The paper is based on an extensive review of literature and insights from key stakeholders across various institutions to evaluate the early foundations of Psychology education, research, and practice in Bangladesh. It highlights significant milestones, the contributions of pioneering figures, and the progress of academic programs while addressing the challenges of integrating Psychology within the country’s sociocultural context. The paper also explores future opportunities for growth in areas such as mental health awareness, policy development, professional training, and the broader application of Psychology in fields like recruitment, licensing, forensic assessment, etc. Despite notable progress, Psychology in Bangladesh continues to face challenges, including inadequate infrastructure, limited funding, insufficient professional recognition, and cultural stigmas surrounding mental health. The paper concludes with strategic recommendations for overcoming these barriers and promoting a more robust and inclusive development of Psychology in Bangladesh, aligning with global standards and local needs. Bangladesh Journal of Psychology, Vol. 24, December 2024, pp. 81-102